1988
DOI: 10.1007/bf00286776
|View full text |Cite
|
Sign up to set email alerts
|

Two routes for 99mTc-DMSA uptake into the renal cortical tubular cell

Abstract: Critical factors determining the renal handling of 99mTc-dimercaptosuccinic acid (DMSA) are protein binding in plasma and the renal 99mTc-DMSA extraction efficiency. Comparison of the count rate over soft tissue with that over the cardiac blood pool about 1 h after injection demonstrated that 99mTc-DMSA is not exclusively an intravascular label. 99mTc-DMSA was 76% protein bound in plasma as demonstrated by HPLC and gel filtration. Assuming that the 24% that is not protein bound is filtered at the glomerulus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 10 publications
0
19
0
1
Order By: Relevance
“…In the case of heavy proteinuria, an altered tracer distribution could be due to the increased glomerular filtration of proteins, leading to increased urinary loss and reduced 99m Tc-DMSA uptake, as reported (36). Conversely, diminished filtration would lead to low 99m Tc-DMSA kidney uptake, even while tubular function is retained, as it is observed under renal artery stenosis and captopril experiments (5,37). Thus, 99m Tc-DMSA renal uptake should also be cautiously interpreted in the case of alterations in glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of heavy proteinuria, an altered tracer distribution could be due to the increased glomerular filtration of proteins, leading to increased urinary loss and reduced 99m Tc-DMSA uptake, as reported (36). Conversely, diminished filtration would lead to low 99m Tc-DMSA kidney uptake, even while tubular function is retained, as it is observed under renal artery stenosis and captopril experiments (5,37). Thus, 99m Tc-DMSA renal uptake should also be cautiously interpreted in the case of alterations in glomerular filtration.…”
Section: Discussionmentioning
confidence: 99%
“…The sodium-dependent dicarboxylate transporter NaDC-3 has been implicated in the basolateral uptake of 99m Tc-DMSA from peritubular capillaries into proximal tubule cells (13). The mechanism by which 99m Tc-DMSA may be reabsorbed from the glomerular ultrafiltrate is unknown; however, studies have indicated that this route may contribute substantially to the renal uptake of the tracer (4,5,14). The potential importance of this pathway is further stressed by recent observations of a decreased renal uptake of 99m Tc-DMSA in patients with proximal tubular endocytic dysfunctions, such as Dent's disease, Lowes syndrome, and Fanconi syndrome (10,15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The 2 postulated mechanisms of 99m Tc-DMSA uptake are peritubular extraction or absorption of plasma protein-bound 99m Tc-DMSA directly from the blood into the proximal tubular cells or glomerular filtration, followed by tubular reabsorption. Discussions on the relative contribution of each of these pathways are ongoing (20)(21)(22)(23)(24)(25)(26). Dynamic imaging of the clearance of radiolabeled diethylenetriaminepentaacetic acid (DTPA) monitors glomerular filtration, because this small molecule is cleared only via this route.…”
mentioning
confidence: 99%
“…Its main metabolic pathway first involves glomerular filtration, followed by tubular reabsorption, with minimal urinary excretion (5%). 2 In adults, its foremost clinical use is to determine differential renal function, but also to image ectopic renal tissue. 3 We have occasionally used Tc-DMSA scans to establish whether a suspected renal mass or pseudomass contains functioning renal tissue or not.…”
Section: Advances In Knowledgementioning
confidence: 99%